Regional convergence and migration in Finland 1960-95 - Pekkala, Sari (2000)
This thesis reports five empirical studies on regional development in Finland. The main focus is on regional economic growth and disparities. The mobility of labour is considered to be one of the decisive factors in determining regional economic structures. Regional migration is thus given a central role in the following chapters. The study seeks to identify what factors have determined the pattern in regional development over the past three decades. The first chapter looks at the development of the Finnish regional economy from 1960s to the present day. Among other factors, trends and developments in regional policy, regional industrial structures, regional equality, movements and concentration of population are described. Second chapter analyses regional GDP growth and convergence at different regional levels and periods, and shows that regional convergence has taken place in Finland. However, its speed has varied greatly in time and across different levels of regional aggregation. Hence the third chapter examines whether these differences in convergence experience are related to aggregate economic fluctuations. It is found that convergence is related to economic upswings, whereas the poorest regions fall mostly behind during recessions. The study of migration as a force affecting regional development is reported in chapter four. The regional characteristics affecting net in-migration positively are the rate of regional income growth and regional education level. Conversely, regions displaying a high level of unemployment tend to suffer from negative net migration, which further slows their economic development. The link between economic growth and migration is analysed in the fifth chapter that tests for the short- and long-run effects of migration on regional growth. It shows that in the short-run migration tends to equilibrate regional income differences, but in the long-run it acts as a disequilibrating mechanism. The final chapter looks into how migrating affects individual post-move incomes and what role regional characteristics and the choice of destination region play in this process. It is found that clear regional differences exist between the Finnish regions in the way in which migrants benefit from moving. Hence, migration affects incomes both at the regional and individual level.